Asprosin in health and disease, a new glucose sensor with central and peripheral metabolic effects - Farrag, Mariam; Ait Eldjoudi, Djedjiga; González-Rodríguez, María; Cordero-Barreal, Alfonso; Ruiz-Fernández, Clara; Capuozzo, Maurizio; González-Gay, Miguel Angel; Mera, Antonio; Lago, Francisca; Soffar, Ahmed; Essawy, Amina; Pino, Jesus; et al. (Frontiers in Endocrinology, 2023)
Adipose tissue malfunction leads to altered adipokine secretion which might consequently lead to an array of metabolic diseases spectrum including obesity, diabetes mellitus, polycystic ovarian syndrome (PCOS), and non-alcoholic fatty liver (NAFLD). Asprosin is a novel diabetogenic adipokine classified as a caudamin hormone protein. This adipokine is released from white adipose tissue during fasting and elicits glucogenic and orexigenic effects. Although white adipose tissue is the dominant source for this multitask adipokine, other tissues also may produce asprosin such as salivary glands, pancreatic B-cells, and cartilage. Significantly, plasma asprosin levels link to glucose metabolism, lipid profile, insulin resistance (IR), and β-cell function. Indeed, asprosin exhibits a potent role in the metabolic process, induces hepatic glucose production, and influences appetite behavior. Generally, clinical and preclinical research showed elevated levels of circulating asprosin in several metabolic diseases such as obesity and type 2 diabetes mellitus (T2DM).